Esophagectomy for esophageal carcinoma - surgical complications and treatment - Vrba, Radek; Aujesky, Rene; Hrabalova, Monika; Vomackova, Katherine; Cincibuch, Jan; Neoral, Cestmir (Biomedical papers, 2012)
Aim: To describe our experience with esophagectomy for esophageal cancer and, the development and treatment of complications arising from the surgery.Material and methods: From 2007 to 8/2010, esophagectomy for esophageal carcinoma was performed in 75 patients at the 1st Surgical Clinic. Primary esophagectomy was indicated in 20 patients with T1N0 stage or in cases where neoadjuvant treatment was contraindicated. 55 patients with T2,3N0,1 stages received neoadjuvant radiochemotherapy. Esophagectomy was performed via an abdominal approach (transhiatal laparoscopy in 44 patients, laparotomy in 3 patients) and a thoracic approach (thoracoscopy in 10 patients, thoracotomy in 18 patients).Results: In 18 cases, one or both pleural cavities were opened by means of dissection of the mediastinal pleura during the transhiatal laparoscopic esophagectomy. The morbidity was 26.6% and the following complications were encountered: pulmonary (15 patients), anastomosis dehiscence (5), postoperative bleeding in the mediastinum (1), fistula between trachea and transposition (1), paresis of the left recurrent nerve (8), infectious complications in the abdominal cavity (2), thoracic cavity (1), and early complications (2). The sixty-day mortality was 8% and this was mostly due to pulmonary complications (4 patients) but included coronary thrombosis (1) and transposition necrosis (1).Conclusion: The dominating complications of esophagectomy were pulmonary (20 %). The remaining serious complications cannot be completely eliminated but if diagnosed in time and treated in a correct algorithm they do not have to imminently threaten the lives of patients.
Keywords: esophageal carcinoma; esophagectomy; treatment complications